A systematic review: Sexual well‐being and perceived barriers to seeking professional help among Chinese adults living with cancer. (10th October 2021) - Chan, Alex; Chang, Hui‐Chen Rita; Alananzeh, Ibrahim; Meedya, Shahla; Green, Heidi; Yan, Zhoumei; Fernandez, Ritin
Abstract: Objective: Sex and intimacy are basic needs and important aspects of quality of life among humans. This focus of this review was to synthesise and present the best available qualitative evidence on the sexual life experiences and needs of Chinese adults living with cancer. Moreover, the first‐hand experience, meaning and perspective about the sexual life changes and support needs during the survival and extended treatment period were synthesised in this study. Methods: A systematic review of qualitative studies was undertaken using the Joanna Briggs Institute System for the Unified Management, Assessment and Review of Information (JBI‐SUMARI). A comprehensive search of five databases: CINAHL, MEDLINE, PubMed, Scopus and Google Scholar were undertaken from 2010 until February 2020 using defined criteria. Methodological quality and data extraction were undertaken using JBI‐SUMARI. Results: Eight studies were included in the review. A total of 39 findings were extracted and aggregated into eight categories based on similarity of meaning. Three synthesised themes were generated: (i) misconceptions and lack of education or information regarding sexual activity exists for patients with cancer, (ii) concerns for overall health and well‐being as well as physical and psychological changes can alter sexual desire and behaviours in patients with cancer and (iii) lack of sexual activity and intimacy can create relationship problems. Conclusions: Sexual relationships are intimate, personal and private in Chinese culture and beliefs. Chinese adults living with cancer report many neglected issues on sexual well‐being in various domains. Adequate and consistent education about sexual intimacy issues from health care providers was identified as an important need. Unaddressed needs might affect adults' coping strategies in managing their sexual relations during various stages of cancer treatment and beyond. It must be noted that there are many Chinese ethnic minorities living with cancer outside the Greater China region. The evidence provides valuable recommendations to health care providers globally to consider the specific sexual needs and initiate culturally sensitive sexuality education and care support for Chinese adults living with cancer.